3 in 1 baby cutie dispenser (BCD) / Siniter Saba ... [et al.] - Saba, Siniter; Mahrif, Nursuria; Othman, Siti Zaidah; Arabi, Arrominy (Universiti Teknologi MARA, Kedah, 2019)
The main objective of this innovative product is to provide a helping hand to parents with small children and babies whilst travelling. This product is known as 3 in 1 Baby Cutie Dispenser; a thermos flask for 500 ml of hot water, a litre for cold water and a 4-compartment milk powder dispenser; holding up to 4 scoops of milk powder. A milk bottle can be inserted in the central unit, attached as one unit. The hot and plain water is dispensed by pressing the top of the bottles, and milk is dispensed by turning the cap of the dispenser. The hot and plain water bottles; made of stainless steel, the 4-compartment milk powder dispenser is made of highly durable plastic. This dispenser is handy and easy to pack. The novelty and uniqueness of this product is it is portable and easy to carry. It may assist students who want to involve in being entrepreneur to market the product to potential parents. The product is divided into 3 compartments to which it will lessen the burden among parents to carry a lot of bags whilst travelling. It has good potential for commercialization as the design looks like a backpack; making it very handy and practical for all walks of working mothers.